NEW ASPECT FOR FIXED POINT THOERY ON ULTRAMETRIC SPACE - Acar, Ö.; Delen, T.; Özkapu, A. S. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2025)
In this paper, we prove some fixed point theorems using different types of contractions with special functions and also give an example to illustrate our results.